2016
DOI: 10.1158/1535-7163.mct-16-0025
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Vemurafenib and Procaspase-3 Activation Is Synergistic in Mutant BRAF Melanomas

Abstract: The development of vemurafenib resistance limits the long-term efficacy of this drug for treatment of metastatic melanomas with the V600EBRAF mutation. Inhibition of downstream MAPK signaling with vemurafenib induces apoptotic cell death mediated by caspase-3, suggesting that addition of a procaspase-3 activator could enhance anticancer effects. Here we show that the combination of PAC-1, a procaspase-activating compound, and vemurafenib is highly synergistic in enhancing caspase-3 activity and apoptotic cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…A considerable number of preclinical studies are investigating other novel targets for overcoming BRAF inhibitor resistance. These include combining BRAF and/or MEK inhibitors with inhibitors of pre-mRNA splicing (to counteract resistance caused by BRAF splicing) [ 251 ], BH3-mimetics [ 252 , 253 ], BCL2 inhibitors [ 254 ], mitochondrial-targeted agents [ 255 , 256 ], inhibitors of p90 ribosomal S6 kinases [ 257 , 258 ], pro-caspase activating compounds [ 259 ], Rho kinase 1 (ROCK1) inhibitors [ 260 ], protein kinase Cδ inhibitors [ 261 ], tubulin inhibitors [ 262 ], ErbB2 or ErbB3 inhibitors [ 222 , 263 , 264 ], activators of the liver-X nuclear hormone receptor [ 265 ], an antibody conjugate targeting the endothelin B receptor [ 266 ], monoclonal antibodies against chondroitin sulfate proteoglycan 4 [ 267 ], inhibitors of sterol regulator element binding protein I (SREBP-1) [ 268 ], copper chelators [ 269 ], polo-like 3 kinase inhibitors (including in models of BRAF + MEK inhibitor resistance) [ 270 , 271 ], anti-nodal antibodies [ 272 ], PAK1 inhibitors [ 273 ], GLI1/2 inhibitors [ 274 ], inhibitors of IQ motif-containing GTPase activating protein 1 (IQGAP1) [ 275 ], serotonin agonists [ 276 ], CK2 inhibitors [ 277 ], p53 activators [ 278 ], metformin [ 279 ], statins [ 280 ], non-steroidal anti-inflammatory drugs [ 281 ], mibefradil [ 282 ], hydroxychloroquine (an autophagy inhibitor) [ 83 ], and A100 (a reactive oxygen species-activated prodrug) [ 283 ].…”
Section: Resultsmentioning
confidence: 99%
“…A considerable number of preclinical studies are investigating other novel targets for overcoming BRAF inhibitor resistance. These include combining BRAF and/or MEK inhibitors with inhibitors of pre-mRNA splicing (to counteract resistance caused by BRAF splicing) [ 251 ], BH3-mimetics [ 252 , 253 ], BCL2 inhibitors [ 254 ], mitochondrial-targeted agents [ 255 , 256 ], inhibitors of p90 ribosomal S6 kinases [ 257 , 258 ], pro-caspase activating compounds [ 259 ], Rho kinase 1 (ROCK1) inhibitors [ 260 ], protein kinase Cδ inhibitors [ 261 ], tubulin inhibitors [ 262 ], ErbB2 or ErbB3 inhibitors [ 222 , 263 , 264 ], activators of the liver-X nuclear hormone receptor [ 265 ], an antibody conjugate targeting the endothelin B receptor [ 266 ], monoclonal antibodies against chondroitin sulfate proteoglycan 4 [ 267 ], inhibitors of sterol regulator element binding protein I (SREBP-1) [ 268 ], copper chelators [ 269 ], polo-like 3 kinase inhibitors (including in models of BRAF + MEK inhibitor resistance) [ 270 , 271 ], anti-nodal antibodies [ 272 ], PAK1 inhibitors [ 273 ], GLI1/2 inhibitors [ 274 ], inhibitors of IQ motif-containing GTPase activating protein 1 (IQGAP1) [ 275 ], serotonin agonists [ 276 ], CK2 inhibitors [ 277 ], p53 activators [ 278 ], metformin [ 279 ], statins [ 280 ], non-steroidal anti-inflammatory drugs [ 281 ], mibefradil [ 282 ], hydroxychloroquine (an autophagy inhibitor) [ 83 ], and A100 (a reactive oxygen species-activated prodrug) [ 283 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of compelling data in mouse models of cancer 64,199,206,209 and m canine cancer patients, 51,199 a phase 1 clinical trial of PAC-1 for late-stage cancer patients was initiated (). Thus far, it has been reported that PAC-1 has excellent pharmacokinetics in human cancer patients (e.g., a half-life of ~20 h 210 ), and PAC-1 has been dosed as high as 750 mg (oral tablet, once-a-day for 21 days) with signs of efficacy in these late-stage cancer patients.…”
Section: Cancer Apoptosis and Procaspase-3mentioning
confidence: 99%
“…By relieving the physiologic labile zinc inhibition of procaspase-3, PAC-1 is able to enhance the ability of procaspase-3 to undergo auto-activation, sensitize the cellular procaspase-3 population to upstream apoptotic signaling events, and enhance the activity of caspase-3 generated through the induction of apoptosis [ 22 , 26 ]. In recent reports PAC-1 has demonstrated dramatic synergy with a number of anticancer agents [ 27 ], most notably with doxorubicin for the treatment of metastatic osteosarcoma [ 26 ], and with vemurafenib for the treatment of mutant BRAF melanoma [ 28 ].…”
Section: Introductionmentioning
confidence: 99%